2014
DOI: 10.1177/0022146513520430
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Depressive Symptoms during Adolescence and Young Adulthood

Abstract: Using longitudinal data from the Toledo Adolescent Relationships Study (TARS), we examine the relationship between intimate partner violence (IPV) and depressive symptoms during adolescence and young adulthood (N = 1, 273) while controlling for time-stable and time-varying correlates. Results show temporal changes in depressive symptoms, such that increases in depressive symptoms correspond to IPV exposure. While prior work has theorized that certain populations may be at increased psychological vulnerability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
71
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 66 publications
4
71
0
1
Order By: Relevance
“…According to numerous authors, the expression “IPV” represents a form of violence that both men and women can enact, with no regard to age, marital status, or sexual orientations (Capaldi et al, 2007; Ali et al, 2016). The consequences of IPV on mental health and general wellbeing have also been outlined in numerous studies (Campbell, 2002; Anderson et al, 2008; Murray and Mobley, 2009; Giordano et al, 2014; Costa et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…According to numerous authors, the expression “IPV” represents a form of violence that both men and women can enact, with no regard to age, marital status, or sexual orientations (Capaldi et al, 2007; Ali et al, 2016). The consequences of IPV on mental health and general wellbeing have also been outlined in numerous studies (Campbell, 2002; Anderson et al, 2008; Murray and Mobley, 2009; Giordano et al, 2014; Costa et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…This is intuitive as hospital in-take records, crime surveys, police logs, and shelter data demonstrated that women typically are the victims of the most severe violence (e.g., Dobash and Dobash, 2004). Yet researchers examining survey data (e.g., Straus, 2008, 2010; Rhoades et al, 2010; Whitaker et al, 2007) including the TARS (e.g., Alvira-Hammond et al, in press; Johnson et al, 2014), and relying on the Revised Conflict Tactics Scale (CTS2) (Straus et al, 1996), found that many women reported that they were violent toward their partners or were involved in bidirectional or reciprocal violence suggesting that victims could be men as well as women. Whitaker, Haileyesus, Swahn, and Saltzman (2007) analyzing the Longitudinal Study of Adolescent Health (Add Health) found that women comprised 70% of perpetrators reporting nonreciprocal violence.…”
Section: Introductionmentioning
confidence: 99%
“…Fergusson, Horwood, and Ridder (2005), specifically analyzing young adults (n = 828), also found that victimization increased men and women’s depressive symptoms. Further, Johnson et al (2014) concluded that any intimate partner aggression (i.e., self-reports of perpetration, victimization, or bidirectional) from early adolescence through young adulthood increased depressive symptoms for both men and women. Thus, based on these studies one conclusion that could be drawn is that victimization leads to depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, personal and interpersonal resilience and thriving depend on the degree to which romantic relationships are either enriching or disruptive (Dmytro, Luft, Jenkins, Hoard, & Cameron, 2013;Friedlander, Connolly, Pepler, & Craig 2013;Johnson, Giordano, Longmore, & Manning, 2014). Much of the current literature on adolescent romantic relationships is focused on the problem of dating aggression and violence, where the perpetrators in heterosexual relationships are usually male.…”
mentioning
confidence: 99%